Faktor-Faktor Yang Berhubungan dengan Tuberkulosis Anak dan Sebarannya di Kecamatan Watumalang Kabupaten Wonosobo Tahun 2011 - Pujiyati Pujiyati; Sri Muryani; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Tuberculosis (TB) is a contagious and chronic disease. This disease still leads to high morbidity and mortality rate in many countries including Indonesia. WHO’s report in 2011, stated that Indo-nesia is the fourth largest country contributing to TB cases in the world. In many developing countries, children aged below 15 years with TB are 15 % of all TB cases. In Kabupaten Wono-sobo, the number of children with TB who seeking care in health centers betwen 2008-2011 were 508, and among the 21 health centers, Watumalang has the highest number of cases. This study was aimed to identify the risk factors and the spread of children with TB in that area by conducting a case-control study. Sample who were derived by total sampling method were 80 children, i.e. 40 in both case and control groups. Data were analysed in univariate, bivariate and multivariate manner. Meanwhile, spatial analysis was conducted by creating a map by using GIS. Bivariat analysis showed that the signifcant factors were: ventilated room (OR=3,444; 95% CI=1,310-9,058); p.value=0,011); contact history (OR= 4,636; 95% CI=1,593-13,494; p.value= 0,003); and nutritional status (OR=13,778; 95% CI=4,713-40,281; p.value<0,001). The further multivariate analysis with logistic regression found that nutritional status was the most dominant factor. Spatially, the cases were distributed around the existed traditional markets as well as the main highway of Wonosobo-Watumalang.